Peran Psikologi Komunikasi Dalam Pembelajaran - Helmi Suardi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Communication psychology in learning aims to describe, predict, and control behavior (behavior) and mental events in student communication. This study uses the literature review method. The issue that frequently emerges in learning is a failure to pay attention to the psychological components of interaction between teachers and students, more specifically to the psychological aspects of communication. Educators are mostly responsible for good and effective communication continuously in learning, so educators are required to have good communication skills so that learning runs effectively. The concept of communication psychology in learning provides an important role as one of the guidelines that influence attitudes, students' thinking, and their behavior regarding knowledge, and perceptions in learning. The concept of communication psychology in learning provides an important role as one of the guidelines that influence attitudes, students' thinking, and their behavior regarding knowledge, and perceptions in learning. Communication psychology is also very instrumental in increasing students' emotional intelligence, influencing the behavior of students, building the effectiveness of communication and building relationships and interpersonal fulfillment. The results show that to overcome the difficulties of educators and students in developing good and effective communication is action, interest, attention, and interpersonal satisfaction.